Desk reference to the diagnostic criteria from DSM-5 - American Psychiatric Association (Washington (D.C.) : American psychiatric publishing, 2013)
The Desk Reference to the Diagnostic Criteria From DSM-5 is a concise, affordable companion to the ultimate psychiatric reference, DSM-5. It includes the fully revised diagnostic classification, as well as all of the diagnostic criteria from DSM-5 in an easy-to-use paperback format. This handy reference provides quick access to the information essential to making a diagnosis. Designed to supplement DSM-5, this convenient guide will assist all mental health professionals as they integrate the DSM-5 diagnostic criteria into their diagnoses. The Diagnostic and Statistical Manual of Mental Disorders stands alone as the most authoritative reference available for clinical practice in the mental health field, and the structural and diagnostic changes in the fifth edition are must-know material for every clinician. The Desk Reference to the Diagnostic Criteria From DSM-5 distills the most crucial, updated diagnostic information from this volume to provide clinicians with an invaluable resource for effectively diagnosing mental disorders, ranging from the most prevalent to the least common.
Includes index.
The Desk reference to the diagnosis criteria from DSM-5 is meant to be used in conjunction with the full DSM-5"
Keywords: Diagnostic and statistical manual of mental disorders; Mental disorders -- Classification; Mental disorders -- Diagnosis; Psychiatrische patiënten; Psychische stoornissen -- Classificatie; Psychodiagnostiek; Psychopathologie